Resistance and accountability - Lehman, Cheryl R. (Advances in public interest accounting ;, 2020)
How do public spaces generate accountability and advance social equity? Stimulating the conversation, the articles in this volume explore the creation of meaning, the increasing confrontation between regulators and the community they are purported to serve, and the prevalent conflicts in seeking a balancing of social and economic interests. How are communities served in hospitals and schools by accounting standards and administrators? Are shareholders protected from managers' opportunistic behaviors? How is professional status supported or denied for women in Columbia and other regions of the globe? Accounting's role in producing worldviews, creating visibilities and in impacting our quality of life stimulates our engagement in these significant issues, reinvigorating what it means to provide accountability. We follow the legacy of public interest and critical accounting research in this volume, uncovering the discipline's relationship to power and symbolism and its impact on our security and well-being as a challenge to conventional accounting.